LEARNING ENGLISH SPEAKING USING ROLE PLAY MODEL FOR SEVENTH GRADERS: A CASE STUDY AT MTS. MAARIF NU TUBAN - Fauzi, Ali; Fathoni Al Maliki, M. Rizky (Tadris : Jurnal Penelitian dan Pemikiran Pendidikan Islam, 2025)
Teaching English Speaking is not so easy that it needs deep thinking to formulate the model. Speaking is considered difficult for the beginners but tecaher can start it little by little. To be effective in teaching speaking, teacher can try by using role play model in which it is rarely used specially in the suburban private secondary school like Islamic Junior High School, MTs. Maarif NU Tuban because it neeeds habit and long practise. Because of it, the researcher suggests him to try to use role play model and is interested to discuss it by choosing the title of research, “Learning English Speaking Using Role Play Model for Seventh Graders: A Case Study at MTs. Maarif NU Tuban.” The researcher wants to know and to describe how the teacher teaches, what approach, strategy, method, media and model he uses during the process of teaching and learning English Speaking. The research is qualitative research in form of case study. The approach he uses is phenomenological approach in which the researcher observes the facts and phenomena during the teaching of English Speaking and he then describes them. The data is in form of information from the teacher, teaching guideline, students’ practice of role play and the facts happening in the classroom during the learning of English speaking. The source of data is taken from text of speaking, interview with the teacher and from the guide books. The method of research is descriptive-qualitative method meaning the researcher just describes his data and his finding during the process of teaching-learning. The result of the research shows that teacher has taught English Speaking using Role Play Model well and successfully. He also applies scientific approach, and model of discovery learning; he uses learning media in form of Dialog Text supported by Guide books or handbooks he has determined. He can manage the class and time of learning well. The students are enthusiastic to join the lesson, motivated to train and to practice English speaking, do the homeworks and can understand the lesson optimally.